Um vagalume suspende o céu: o “Taller de cine para niños” de Alicia Vega - Verônica Pacheco de Oliveira Azeredo (2021)
The study carried out between March 2017 and May 2021 in Chile and Brazil describes and records some of the elements that outline the “Taller de Cine para Niños” created and developed by Alicia Vega between 1985 and 2015. The study inquires whether a “Pedagogia Alicia” is contained in it considering mostly the conceptions and principles that inspire it and the undertaken activities. Alicia is part of a story of Chilean women especially, those who worked with cinema and education in the Latin America. For 30 years, this professor of cinematographic language, researcher and book author taught cinema for 6378 poor children from the outskirts of Chile. A three-way research methodology was adopted: in-person narrative interviews carried out with Alicia Vega, and monitors and professionals who participated in the Talleres; document research from several sources including written and visual files and archives, documentary, videos, photographic collection, reports, books, and others, from Chile and Brazil; and direct observation in Santiago, Chile. Inspired by the metaphor of the firefly from Didi Huberman (2011), by the idea of lift up the sky from the tradition of native people, retaken by Ailton Krenak (2019), and by the train which arrives, from Ignácio Aguero’s documentary (1987), the thesis concludes that these formulations express what happened there. By the hands of Alicia, a firefly, with no spotlights, the niños and niñas from the Talleres flied way beyond their places of Chilean poor children, travelling far away pursuing their right to access art. On this trip, we see them expanding their human and aesthetic experiences when they come across cinema which made possible to admire the “Pegadogia Alicia”: in the scenario, the script, the scenes, the plots and plans there assembled. In Vega’s boards among children, on the cinema train, among centipede frames and a lot more, it was possible to see fireflies lift up the sky.